The female geriatric proximal humeral fracture: protagonist for straight antegrade nailing? - Lindtner, Richard A. (Arch Orthop Trauma Surg, 2017)
INTRODUCTION: Straight antegrade humeral nailing (SAHN) has become a standard technique for the surgical fixation of proximal humeral fractures, which predominantly affect elderly females. The nail’s proximal anchoring point has been demonstrated to be critical to ensure reliable fixation in osteoporotic bone and to prevent iatrogenic damage to the superior rotator cuff bony insertion. Anatomical variations of the proximal humerus, however, may preclude satisfactory anchoring of the nail’s proximal end and may bare the risk of rotator cuff violation, even though the nail is inserted as recommended. The aim of this study was to evaluate the anatomical suitability of proximal humeri of geriatric females aged 75 years and older for SAHN. Specifically, we sought to assess the proportion of humeri not anatomically amenable to SAHN for proximal humeral fracture. MATERIALS AND METHODS: A total of 303 proximal humeri of 241 females aged 75 years and older (mean age 84.5 ± 5.0 years; range 75–102 years) were analyzed for this study. Multiplanar two-dimensional reformations (true ap, true lateral, and axial) were reconstructed from shoulder computed tomography (CT) data sets. The straight antegrade nail’s ideal entry point, “critical point” (CP), and critical distance (CD; distance between ideal entry point and CP) were determined. The rate of proximal humeri not anatomically suitable for SAHN (critical type) was assessed regarding proximal reaming diameters of currently available straight antegrade humeral nails. RESULTS: Overall, 35.6% (108/303) of all proximal humeri were found to be “critical types” (CD <8 mm) as to the recommended minimal proximal reaming diameter of 10 mm of straight antegrade nails currently in use. Moreover, 43.2% (131/303) of the humeri were considered “critical types” with regard to the alternatively used larger proximal reaming diameter of 11.5 mm. Mean CD was 9.0 ± 1.7 mm (range 3.5–13.5 mm) and did not correlate with age (r = −0.04, P = 0.54). No significant differences in CD and rate of “critical types” were found between left and right humeri as well as between females aged between 75 and 84 years (n = 151) and females aged 85 and older (n = 152). CONCLUSIONS: More than a third of proximal humeri of geriatric females are “critical types” as to SAHN and may, therefore, be at risk for procedure-related complications, such as rotator cuff violation, fixation failure, and potential malreduction. In view of this finding, we recommend to routinely analyze multiplanar CT reformations of the uninjured contralateral side prior to surgery to improve selection of patients for SAHN and to minimize foreseeable complications. For “critical type” humeri, an alternative surgical procedure should be considered.